Organisation of Ukrainian Nationalists on emigration - Gibiec, Magdalena, author.
1 online resource.
Keywords: "This book describes the formation, transnational activities, and inner workings of the Organization of Ukrainian Nationalists (OUN) in exile. Made possible thanks to an in-depth examination of previously unutilised correspondence relating to the OUN, this title examines the organization during the first five years of its existence (1929-1934). In contrast to other available sources, such as the press or propaganda materials, the letters more faithfully present actual plans, motivations, and goals of the nationalists. The analysis not only uncovers unknown facts, but also reveals reactions, opinions, and emotions of individual activists. The book explores the structure and mechanisms of the OUN émigré networks by depicting tactics, decision making processes, and the efficiency of activities, as well as contacts and relations within the OUN and with the outside world. The international activity of the OUN is examined through the cooperation with individual countries, including Lithuania, Czechoslovakia, and Germany, but also with lobbying efforts in Great Britain, France, Italy, and North America, where émigré activists of the OUN or their contacts were based. Finally, the book investigates the OUN policy towards activists operating on the area of the Second Polish Republic. This text will be of interest to scholars of Ukrainian history, nationalism, comparative fascism, and transnationalism"--